Deep brain stimulation for Holmes' tremor related to a thalamic abscess - (:unkn) unknown (SPRINGER, 2008)
Background Medical treatment is usually ineffective for Holmes' tremor, and surgery is the treatment of choice for many patients. Here we report the case of a 14-year-old girl who developed Holmes' tremor related to a thalamic abscess and was successfully treated with thalamic deep brain stimulation. Case report The patient presented with left hemiparesis and headache and was hospitalized. Investigation revealed a thalamic abscess in the left cerebral hemisphere. The abscess was drained via stereotactic surgery and a course of antibiotic treatment was completed. Four months after treatment, the patient developed Holmes' tremor in her left upper extremity. When attempts at medical treatment with levodopa, clonazepam, and trihexyphenidyl all failed, an implant was placed and deep brain stimulation of the ventral intermediate nucleus of the thalamus was initiated. During 2.5 years of follow-up, her tremor diminished by 90%. Conclusion This case demonstrates that medically resistant Holmes' tremor related to a thalamic lesion can be successfully treated with thalamic deep brain stimulation.
Keywords: deep brain stimulation; Holmes' tremor; midbrain tremor; thalamus; ventral intermediate nucleus; VENTRALIS INTERMEDIUS; MIDBRAIN TREMOR; RUBRAL TREMOR; THALAMOTOMY; SECONDARY